2017
DOI: 10.29088/gmjm.2017.15
|View full text |Cite
|
Sign up to set email alerts
|

Carvacrol Alleivated Negative Effects of Diabetes on Inflammation and Oxidation by Modulation in Gene Expression of Inflammatory and Antioxidant System in Diabetic Rat Model

Abstract: Background: Diabetes has been known as a prevalence disorder and the use of common drugs has been faced many issues with multiple limitations. This study aimed to evaluate the use of carvacrol, as a novel agent, for treatment of diabetes. Materials and Methods:A single dose of streptozotocin (55 mg/kg body weight) was used to induce the diabetes in rats. The animals were grouped into five groups including 1. Control healthy animals; 2. Diabetic controls; 3, 4 & 5. Diabetic animals given carvacrol (5, 10 and 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…Hypertriglyceridemia, hypercholesterolemia, hyperglycemia, and hypoinsulinemia could be due to an increase in TNF-α. It steps up triglyceride production in plasma29 and cuts down glucose consumption in peripheral tissues by targeting insulin signaling pathways and the glucose transporter 4 (GLUT4) 3,30. Parallel to our findings, Kido et al13 have reported that high intake of alcoholic beverages with a meal causes different responses in postprandial glucose and insulin concentrations.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Hypertriglyceridemia, hypercholesterolemia, hyperglycemia, and hypoinsulinemia could be due to an increase in TNF-α. It steps up triglyceride production in plasma29 and cuts down glucose consumption in peripheral tissues by targeting insulin signaling pathways and the glucose transporter 4 (GLUT4) 3,30. Parallel to our findings, Kido et al13 have reported that high intake of alcoholic beverages with a meal causes different responses in postprandial glucose and insulin concentrations.…”
Section: Discussionsupporting
confidence: 84%
“…The diagnosis of diabetes mellitus is usually based on hyperglycemia and glucose intolerance 2. Increased blood glucose, insulin resistance, and rising inflammatory markers have been reported in patients with diabetes mellitus 3. Regarding inflammatory factors, a positive relation between levels of proinflammatory cytokines, including tumor necrosis factor-α (TNF-α) and IL-6, and insulin resistance has been found 4,5.…”
Section: Introductionmentioning
confidence: 99%
“…Tabibzadeh Dezfuli et al (2017) also demonstrated that oral administration of carvacrol, once daily, in animals with streptozotocin (STZ)-induced diabetes, reduces the levels of IL-1β, IL-6m and TNF-α [120]. On the other hand, contradictory results were obtained, claiming that carvacrol has a positive effect in reducing IL-1β, IL-4, and IL-8, but would not have an effect on IL-6 and TNF-α, probably due to the methodology used in the studies by de Carvalho et al (2020) [119,121].…”
Section: Anti-inflammatory Effects Of Carvacrol and Magnololmentioning
confidence: 99%
“…In research by Tabibzadeh Dezfuli et al ( 2017) it was shown that oral administration of 15 mg/kg body carvacrol, per day, to diabetic rats, can lower malondialdehyde (MDA) levels and increase CAT, SOD, and GPx activity, compared to rats to whom the extract has not been administrated, suggesting that carvacrol has antioxidant properties [120].…”
Section: Antioxidant Properties Of Carvacrol and Magnolol In Association With Periodontal Disease And Diabetes Mellitusmentioning
confidence: 99%
See 1 more Smart Citation